Chronotypes of Bipolar Patients in Remission: Validation of the French Version of the Circadian Type Inventory in the FACE-BD Sample. (17th July 2013) - Boudebesse, C.; Lajnef, M.; Geoffroy, P. A.; Bellivier, F.; Nieto, I.; Gard, S.; Olié, E.; Azorin, J. M.; Kahn, J. P.; Bougerol, T.; Passerieux, C.; Aubin, V.; et al.
Abstract : Circadian rhythm disturbances have been associated with bipolar disorder (BD) during both the mood episodes and the periods of remission. Circadian phase preferences for the evening have been reported for remitted patients, whereas the amplitude and stability of their rhythms have never been assessed using questionnaires. The primary aim of our study was the validation of a French version of the Circadian Type Inventory (CTI), whereas its secondary aim was the comparison between remitted patients with BD and healthy controls for rhythm stability and amplitude and for phase preference. For this purpose, we used the CTI and the Composite Scale of Morningness (CSM) that assesses phase preference ("morning" or "evening" type). First, we report here on the validation of the French version of the 11-item Circadian Type Inventory in a sample of 140 remitted patients with BD and 156 healthy controls. Principal components analysis revealed a two-factor structure (FR: flexibility/rigidity scale corresponding to rhythm stability; LV: languid/vigorous scale corresponding to rhythm amplitude) explaining 52% of the variance in the control group and 47% in the bipolar group. Cronbach's alpha was 0.75 for FR and 0.73 for LV. The test-retest reliability was 0.74 for FR and 0.86 for LV (3 wks) and 0.62 for FR and 0.72 for LV (6 mos). LV and FR scores correlated with the Composite Scale of Morningness score ( p <  0.00001 and p =  0.0002, respectively). Second, as compared with controls, patients with BD were more languid ( p  < 0.00001) and showed an evening preference ( p =  0.0003), but they did not differ from the controls with regard to flexibility/rigidity. The French version of the CTI appeared to have satisfactory psychometrics characteristics. Bipolar patients exhibited not only abnormalities in phase preference but also in amplitude as measured by languidity. Since circadian rhythm dysfunction has been shown to predict poor functioning and mood relapses in interepisodic patients with BD, this tool would appear to be a promising, easy-to-use, measure of the amplitude and flexibility of circadian rhythms that could enrich the arsenal of assessments used in clinical settings.